Becik Ketitik Ala Ketara Cultural Values For Public Accountants And Audit Opinion Determination Decisions - Fitri Ahmad Kurniawan; Rizqia Karunianing Illahi (JAFFA, 2022)
This study explores the existence of the “Becik Ketitik Ala Ketara” culture within the Public Accountant. The cases experienced by public accountants have forced researchers to explore the existence of national culture as a support for the 2020 Code of Ethics for the Professional Public Accountant (KEPAP). This study objectively reveals the reality of the existence of the “Becik Kedot Ala Ketara” culture within the Public Accountant in making audit opinion decisions. This study uses a realist ethnographic method with participatory observation and interview data collection techniques. The results of the study show that the cultural values of becik to the point of being clearly exist or are used by public accountants to underlie ethical attitudes when setting audit opinions. There are four cultural values of “Becik Kedot Ala Ketara” becik (good) that are applied by public accountants, including the words of sabda pandhita ratu, rereh, ririh, lan ngati-ati, deduga lawan prayoga, and nora amung mbujeng kalahiran.